Preface - RUSINEK, Alexis; LODYGOWSKI, Tomasz (Engineering Transactions, 2015)
Professor George Z. Voyiadjis is the Boyd Professor at the Louisiana State University, in the Department of Civil and Environmental Engineering. This is the highest professorial rank awarded by the Louisiana State University System. He is currently the Chair of the Department of Civil and Environmental Engineering. He currently also serves since 2012 as the Director of the Louisiana State University Center for GeoInformatics.